Analysis of Factors Affecting Economic Growth in Lombok Barat Regency, Nusa Tenggara Barat Province for the Period 2012 - 2022 - Ni Nengah Budi Apriyantini; Sahri , Sahri; Tuti Handayani (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
Each region has different growth drivers depending on the region's ability to produce goods and services. This study aims to analyse the effect of population, government expenditure, foreign investment, and domestic investment partially and simultaneously on economic growth in Lombok Barat Regency, Nusa Tenggara Barat Province in 2012-2022. This study uses time series data on population, government expenditure, foreign investment, and domestic investment for 11 years. In addition, this study uses multiple linear regression analysis method as the analytical tool used. The results of this study indicate that the variables of population, foreign investment, and domestic investment partially have a negative and insignificant effect on economic growth in Lombok Barat Regency. While the Government Expenditure variable partially shows that the variable has a positive and insignificant effect on economic growth in Lombok Barat Regency. Simultaneously, the influence of population, government expenditure, foreign investment, and domestic investment variables has an insignificant effect on economic growth in Lombok Barat Regency.